Association study reveals a susceptibility locus with male pattern baldness in the Han Chinese population - Li, Yang; Huang, He; Liang, Bo; Xiao, Feng-Li; Zhou, Fu-Sheng; Zheng, Xiao-Dong; Yang, Sen; Zhang, Xue-Jun (Frontiers in Genetics, 2024)
Introduction: Male pattern baldness (MPB), also known as androgenetic alopecia, represents the most prevalent form of progressive hair loss in humans. It is characterized by a distinctive pattern of hair loss progression from the scalp; however, its underlying mechanism remains elusive and is influenced by hereditary, immune, and environmental factors. Genome-wide association studies (GWASs) have uncovered numerous risk genes/loci among European individuals with MPB. However, the validation of these susceptibility genes/loci within Han Chinese men remains largely unexplored. The aim of this study was to investigate whether the 71 susceptibility loci identified in a recent GWAS among European men also confer risk for MPB in Chinese men. Methods: Forty-seven single nucleotide polymorphisms (SNPs) previously reported in GWASs of MPB were selected and genotyped in independent individuals comprising 499 Han Chinese cases and 1489 controls using the Sequenom MassArray system. After stringent quality control measures, 25 SNPs were subjected to statistical analyses. Cochran–Armitage trend test was used to evaluate the association between SNPs and disease susceptibility. To address multiple tests, Bonferroni correction was conducted, setting the threshold for statistical significance at a P value < 2×10-3 (0.05/25). Results: The rs13405699 SNP located at 2q31.1 exhibited a significant association with MPB in Han Chinese men (P = 4.84×10-5, OR = 1.37, 95% CI: 1.18–1.59). Moreover, the difference in rs13405699 genotype distribution between MPB cases and controls was statistically significant (P = 7.00×10-5). Genotype-based association analysis suggested that the recessive model provided the best fit for the rs13405699 polymorphism. Conclusion: This study represents the first confirmation of the association between the rs13405699 SNP at 2q31.1 and MPB within the Han Chinese population, thereby enhancing our understanding of the genetic underpinnings of MPB.